2014
DOI: 10.1007/s12639-014-0443-5
|View full text |Cite
|
Sign up to set email alerts
|

Sero-epidemiological value of some hydatid cyst antigen in diagnosis of human cystic echinococcosis

Abstract: Cystic echinococcosis (CE) is a severe zoonotic disease which affects both human and animals. The disease has a considerable economic and social impact, because it has numerous complications leading to important disabilities and even death. CE is a widespread chronic endemic helminthic disease caused by infection with metacestodes of tapeworm Echinococcus granulosus. This study was conducted to diagnosis human CE by hydatid cyst antigens from camels and sheep. Hydatid fluid and protoscoleces crude antigens cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…However, CE is still a common health problem in developing countries, particularly in rural areas [28]. Community-based studies have demonstrated that the prevalence of human CE is between 1% and 10% in endemic regions [14]. Notably, 22.6% of slaughtered camels came from the Northern and Southern Egyptian slaughterhouses [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, CE is still a common health problem in developing countries, particularly in rural areas [28]. Community-based studies have demonstrated that the prevalence of human CE is between 1% and 10% in endemic regions [14]. Notably, 22.6% of slaughtered camels came from the Northern and Southern Egyptian slaughterhouses [29].…”
Section: Discussionmentioning
confidence: 99%
“…The use of crude hydatid cyst antigens in serological diagnostic tests is inadequate. Thus, the purification of hydatid cyst antigens excludes other cross-reactive proteins [14]. Many types of electrophoretic analysis have been used to purify hydatid antigens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Egypt, many authors dealt with the definitive host, mainly dogs, cattle, slaughtered an-imals and human infection as well as the medical and surgical treatment (Handousa, 1951;Haridy et al, 1998;2000, 2008El Shazly et al, 2007a;Aaty et al, 2012;Hassanain et al, 2016;Aldahmashi et al, 2016; and others) Conclusion It is important to consider parasitic infections in the differential diagnosis of such lung diseases. If identified early, most parasitic diseases that affect the lung are curable with medical or surgical treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The cyst fluid (CF) and protoscolex proteins of Eg had been evaluated and proved to be valuable antigens for the CE serological diagnosis [16,22,24]. However, sensitivities and specificities of these antigen proteins differ greatly, and some of the cyst fluid antigen components such as metabolites and host tissue components can cross-react with nonspecific antibodies that target other worms, resulting in poor specificity [15,22]. Golassa et al [17] evaluated the diagnostic value of crude cyst fluid in bovine CE via indirect hemagglutination test (IHA) and found that the false positive and false negative rates were high, and the accuracy is relatively low.…”
mentioning
confidence: 99%